Does Fetal Fibronectin Predict the Delivery Route in Nulliparous Women at Postterm Induced by Dinoprostone? - Hale Goksever Celik; Engin Celik; Gonca Yetkin Yildirim (Gynecology Obstetrics & Reproductive Medicine)
Objective: Digital cervical evaluation has been used to determine the likelihood of vaginal delivery which is considered by many women to be non-tolerable. Recently, alternative approaches such as transperineal ultrasound, fetal fibronectin test in cervicovaginal secretions have been investigating for the prediction of the delivery route. We aimed to study whether the usefulness of qualitative fetal fibronectin test in cervicovaginal secretions for the prediction of vaginal delivery in pregnant women at postterm induced with dinoprostone.